Political Competition and the Strategic Adoption of Free Trade Agreements - Emanuel Ornelas (CESifo GmbH, 2024)
I study how political competition affects the feasibility of free trade agreements (FTAs). I show that the possibility of political turnover creates strategic motivations for the formation of FTAs. Specifically, a government facing a high enough probability of losing power will have an incentive to form a trading bloc to "tie the hands" of its successor. This incentive mitigates inefficiencies in the incumbent's decision to form FTAs, regardless of its bias toward special interests. An FTA can affect the likelihood of political turnover as well. Accounting for that effect, I show that an incumbent party with a known bias toward special interests could seek an FTA as a commitment device toward less distortionary policies, thereby enhancing its own electoral prospects. Overall, the analysis reveals the importance of considering the time horizon of policymakers when studying their decision to enter in FTAs.
Keywords: F15; F13; D72; 330; regionalism; free trade agreements; political competition; lobbying